Online Depression Communities: Does Gender Matter? - Galit Nimrod (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2012)
While women are at a greater risk for depression, men with depression are at a greater risk for mistimed and inadequate treatment. Online depression communities offer immediate support for both genders, and may reduce the risk for those depressed men who avoid the traditional mental healthcare system. This study aimed to explore gender differences among members of online depression communities. Based on an online survey of 793 members of 16 online depression communities, the study combined both behavioral and psychological measures. The results identified significant gender differences in members’ self-defined condition, participation patterns, interests and reported benefits. Additional differences were found in the associations between the main differentiating variables and the members’ level of depression. The findings indicated that women in online depression communities are more involved and report more benefits from participation than men. However, active participation may be even more beneficial for men than for women, as it may provide positive change not only in their general sense of well-being, but also in their clinical condition. Using strategies for promoting active participation among men may enhance the benefits they gain from the online communities.